Innovation in Organic Waste Utilization by PLTGU PT Cikarang Listrindo Tbk to Support the Food Security Program in Wanajaya Village, Cibitung Subdistrict, Bekasi Regency - Pradipta, Ganuardi; Kandioh, Beverly; Vicky Ardhitya Mahadewa; Muhamad Rai Jemadila; & Ida Parsaulian Sihombing (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
Organic waste management is a strategic issue in promoting sustainable development, particularly in densely populated and industrial areas such as Bekasi Regency. This study aims to describe the innovation in organic waste utilization by PLTGU PT Cikarang Listrindo Tbk in supporting the food security program in Wanajaya Village. The key issues examined include the high volume of organic waste, its utilization potential, and the role of the industrial sector in sustainable waste management. This research adopts a descriptive qualitative approach with data obtained through interviews, field observations, and documentation. The findings reveal that the company’s initiative to process organic waste into compost has significantly improved the quality and productivity of local organic farming. This innovation not only strengthens food security but also reduces farmers’ operational costs, and promotes active community participation in environmental management. The program demonstrates the tangible contribution of the private sector in supportingthe Sustainable Development Goals, particularly SDGs Number 2 (Zero Hunger) and SDGs Number 12 (Responsible Consumption and Production).